Comparing cost of intravenous infusion and subcutaneous biologics in COVID‐19 pandemic care pathways for rheumatoid arthritis and inflammatory bowel disease: A brief UK stakeholder survey. Issue 9 (8th July 2021) - Heald, Adrian; Bramham‐Jones, Steven; Davies, Mark
Abstract: Objectives: One important group of people at higher risk from the SARS‐CoV‐2(COVID‐19) pandemic are those with autoimmune conditions including rheumatoid arthritis/inflammatory bowel disease. To minimise infection risk, many people have been switched from intravenous to subcutaneous biologics including biosimilars. Design: The survey was designed to understand comparative economic issues related to the intravenous infusion vs subcutaneous biologic administration routes for infliximab. The survey focused on direct cost drivers/indirect cost drivers. Acquisition costs of medicines were not included due to data not being available publicly. Wider policy implications linked to the pandemic were also explored. Setting/participants: Semistructured single telephone interviews were carried out with twenty key stakeholders across the National Health Service(NHS) from 35 clinical/42 pharmacy/28 commissioning roles. The interviews were undertaken virtually during April 2020. From interview (n = 20) results, a simple cost analysis was developed plus a qualitative analysis of reports on wider policy/patient impacts. Results: Key findings included evidence of significant variation in local infusion tariffs UK wide, with interviewees reporting that not all actual costs incurred are captured in published tariff costs. A cost analysis showed administration costs 50% lower in the subcutaneous compared to infusion routes, with most patients administering subcutaneous medicines themselves. Other indirect benefits to this route included less pressure on infusion unit waiting times/reduced risk of COVID‐19 infection plus reduced patient 'out of pocket' costs. However, this was to some extent offset by increased pressure on home‐care and community/primary care services. Conclusions: Switching from infusion to subcutaneous routes is currently driven by the COVID‐19 pandemic in many services. A case for biologics (infusion vs subcutaneous) must be made on accurate real‐world economic analysis. In an analysis of direct/indirect costs, excluding medicine acquisition costs, subcutaneous administration appears to be the more cost saving option for many patients even without the benefit of industry funded home‐care. What's known: One important group of people at high risk in COVID‐19 pandemic are those with autoimmune conditions, including those with rheumatoid arthritis and inflammatory bowel disease. Depending on the complexity of their condition, some of the patients in this group may be receiving intravenous biologic infusion therapy which under normal circumstances is administered within a hospital or day hospital setting. The National Institute for Health and Care Excellence has published new guidance to ensure that patients having intravenous treatment are assessed for possible switching to the same treatment in subcutaneous form. What's new: A cost analysis showed that administration costs for subcutananous routes are 50% lower than for infusion routes, with most patients administering subcutaneous medicines themselves. Other indirect benefits to this route included less pressure on infusion unit waiting times and reduced risk of COVID‐19 infection, along with reduced patient costs. Cost savings were partly offset by increased pressure on home‐care and community/primary care services.